DEVELOPING FINTECH AND ISLAMIC FINANCE PRODUCTS IN AGRICULTURAL VALUE CHAIN - R. Gratiyana Ningrat; Mohamad Soleh Nurzaman (Journal of Islamic Monetary Economics and Finance, 2019)
To meet the global population needs, it is projected to at least eighty billion dollars in investment per year to support the food security until 2050. It is widely known that the agriculture financing growth has stalled due to many reasons. Islamic finance has potential to spur the growth of agriculture financing to promote global food security. Meanwhile, agriculture in Indonesia is still nowhere to its potential. It is hindered by an inefficient and underdeveloped downstream segment, low access to financial and technology. This is a huge opportunity for Islamic finance in helping to bridge the gap through value chain finance approach as one of the strategies to reduce risk and give socio-economic spill-over effect along the chain. Islamic finance can promote agricultures sustainability and a more efficient process with FinTech enabled platform. The multiple case study proposes a sharia compliant community-based financing model in agricultural value chain practice with FinTech enabled platform. The result is this model integrating all actors from different market segmentation (landowners, suppliers, farmers, brokers, retailers, investor) into an Islamic value chain financing platform. However, determining buying intention, partnership establishment, and technology infrastructure are pivotal for its future implementation.